2014
DOI: 10.1371/journal.pone.0090302
|View full text |Cite
|
Sign up to set email alerts
|

Industry-University Collaborations in Canada, Japan, the UK and USA – With Emphasis on Publication Freedom and Managing the Intellectual Property Lock-Up Problem

Abstract: As industry-university collaborations are promoted to commercialize university research and foster economic growth, it is important to understand how companies benefit from these collaborations, and to ensure that resulting academic discoveries are developed for the benefit of all stakeholders: companies, universities and public. Lock up of inventions, and censoring of academic publications, should be avoided if feasible. This case-study analysis of interviews with 90 companies in Canada, Japan, the UK and USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…For example, previous studies have found that some trial agreements permit funders to block publication. 5 6 7 8 Furthermore, academics have reported problems with stalling of publications, restriction of publication rights, and threats to never fund their institution again owing to reporting of negative results or harms. 9 A survey of Canadian trial investigators found problems in relation to industry control over study design, ownership of and access to data, and data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies have found that some trial agreements permit funders to block publication. 5 6 7 8 Furthermore, academics have reported problems with stalling of publications, restriction of publication rights, and threats to never fund their institution again owing to reporting of negative results or harms. 9 A survey of Canadian trial investigators found problems in relation to industry control over study design, ownership of and access to data, and data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Online survey with a sample size of 402 respondents. Kneller, Mongeon, Cope, Garner, and Ternouth (2014) To assess industry-university collaborations to understand how companies benefit from these collaborations, and to gauge how academic discoveries benefit all stakeholders: companies, universities and the public.…”
Section: A Social Capital University-industry Knowledge Transfer Frammentioning
confidence: 99%
“…The volume of corporate R&D activities can be measured in different ways; for example, by counting the number of patents and/or the number of patent citations (Narin et al, 1987;Chang et al, 2012;Liu et al, 2006;Ribeiro et al, 2010;Ribeiro et al, 2014;Wang et al, 2011;Wong, Wang, 2015); by counting the amount in R&D expenditures (Granstrand, 1999;Kumar, 2001;Piergiovanni, Santarelli, 2013;Yoo, Moon, 2006); by defining the quantity and quality of research cooperation between firms and universities (Feng et al, 2015;Gao et al, 2011;Kneller et al, 2014;Ramos-Vielba et al, 2010); and by the number of scientific articles authored or coauthored by researchers within the firms (Chang, 2014;Furukawa, Goto, 2006;Hicks et al, 1994;Hicks, 1995;Hullmann, Meyer, 2003;Tijssen, 2004;Csomós, Tóth, 2016a). The latter method is confirmed by Narin et al (1987: 144), who addressed the product life cycle of corporations: "Corporate sales lead to corporate profits, which may be used in research and development to produce scientific innovations (scientific publications), which may lead to technological innovations (some of which will be patented), which is the catalyst for new products and more efficient processes, which will increase corporate profits.…”
Section: How Can Corporate Randd Activities Be Measured?mentioning
confidence: 99%